Robotics : modelling, planning and control - Siciliano, Bruno (Springer, 2017)
The classic text on robot manipulators now covers visual control, motion planning and mobile robots too! Robotics provides the basic know-how on the foundations of robotics: modelling, planning and control. The text develops around a core of consistent and rigorous formalism with fundamental and technological material giving rise naturally and with gradually increasing difficulty to more advanced considerations. The theory of manipulator structures presented in the early part of the book encompasses: • the fundamentals: kinematics, statics and trajectory planning; and • the technology of actuators, sensors and control units.